EVALUATION OF BETA-ADRENOBLOCKERS TREATMENT IN CARDIOVASCULAR DISEASES COMORBID WITH DIABETES IN OUTPATIENT SETTING - N. A. Komkova; A. V. Zagrebelny; Yu. V. Lukina; M. M. Lukyanov; A. N. Vorobyov; К. G. Pereverzeva; N. P. Kutishenko; N. V. Kiseleva; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
2 FSBEIHEI.P. PavlovRyazanskyStateMedicalUniversity. Ryazan,RussiaAim. To evaluate the practice of beta-blockers (BB) usage in cardiovascular disease (CVD) patients with diabetes (DM) in two outpatient registries.Material and methods. Registry PROFILE is the patients (n=1531) with CVD, visited specialized cardiological department of medical research center of Moscow during the period 2011-2015, and registry RECVAZA — patients (n=3690), visited 3 city polyclinics in Ryazan city in 2012-2013. Number of DM patients is 221 (14,4%) in PROFILE and 699 (18,9%) in RECVAZA.Results. In the RECVAZA, the rate of BB prescription was almost the same in CVD and DM; in PROFILE there was significantly more frequent prescription of BB, especially after myocardial infarction (86,4%) and in chronic heart failure (72,6%). In both registries bisoprolol was in use most commonly: 61,8% in PROFILE and 75,4% in RECVAZA. Among DM patients, not taking BB, in PROFILE registry there were additional contraindications: chronic obstructive pulmonary disease and asthma, than in RECVAZA.Conclusion. Clinicians of the specialized cardiological department, comparing to clinicians in local outpatient institutions more actively prescribed BB to DM patients, especially in the cases when this could improve long-term outcomes of the disease. This matches with recent clinical guidelines.